ADAPATASI BEBERAPA VARIETAS PADI (Oryza sativa L.) PADA TANAH SALIN - Satriya Sandi Kurniawan; Lollie Agustina P Putri; Mbue Kata Bangun (Jurnal Agroekoteknologi, 2013)
ABSTRACT One way to effort increase rice production is to expend the cultivation area of rice on saline soil, so it needs to test of some varieties in order the varieties can adaptation. This research aims to obtain varieties of rice (Oryza sativa L.) that can be adapted to saline soil. The research was conducted in the Desa Serdang, North Sumatera at ± 1 m altitude above sea level and 1.5 – 2 km from the beach. The research was carried out in May until October 2011. The design of the experiment was randomized block design with 18 varieties that carried out a preliminary test before, in order get 5 varieties that can adapted to saline soil. The results showed that 5 varieties can adapted to the saline soil is Banyuasin, Siakraya, Martapura, Dendang, and Margasari. Martapura was better than the other varieties on plant height, number of tillers, number of productive tillers, panicle length, wet weight of roots and grain productions parameter. Key words : rice, varieties, saline